Bovine lactoferrin induces cell cycle arrest and inhibits mTOR signaling in breast cancer cells - Zhang, Yunlei (2014)
Lactoferrin (LF) is predominantly found in mammalian secretions with recognized anticancer potential, although the mechanisms involved in such activity are still unclear. Here, the stability, internalization, and cytotoxicity of bovine LF (bLF) and its variants were tested against a panel of breast cancer cells. bLF was found to be very stable under incubation with cells and also able to internalize them, although most of the protein remained in the culture medium. Furthermore, bLF (up to 30 μM) inhibited the growth of breast cancer cells (T-47D, MDA-MB-231, Hs578T, and MCF-7) in a higher extent than in the normal counterpart cell line (MCF-10-2A), thus suggesting its selectivity. Regarding its variants, only the iron-saturated protein showed a higher activity compared with the commercial bLF. bLF growth inhibitory activity was associated with the induction of cell cycle arrest, but not with apoptosis. Moreover, exposure to bLF increased the cells phospho-AMPKα levels and decreased both phospho threonine mammalian target of rapamycin (mTOR) and total mTOR levels, indicating a novel mechanism of action through its ability to induce nutrient/energy-related stress. This study disclosed important findings to better understand the mechanisms underlying the bLF effects on breast cancer cell lines, which could be valuable for novel advances in the cancer research field.